Prevalence of malocclusion and orthodontic treatment needs among young adults in Jeddah city - Yahya A Alogaibi; Zuhair A Murshid; Fahd F Alsulimani; Amal I Linjawi; Mona Almotairi; Mariana Alghamdi; Hussein Alharthy; Ali A Hassan (Wolters Kluwer Medknow Publications, 2020)
OBJECTIVE: To assess the prevalence of malocclusion and orthodontic treatment needs in a Saudi sample of Jeddah city. MATERIALS AND METHODS: A cross-sectional (descriptive) study was performed in 2017 among 3016 subjects (1507 females and 1509 males) selected according to stratified random sampling design. The inclusion criteria were Saudi students aged between 14-18 years with no craniofacial deformities or syndromes and no orthodontic treatment carried out. Malocclusion was assessed using the modified Bjork et al. system, and Angle's classification and orthodontic treatment need to be evaluated by using the IOTN (DHC). Descriptive, associations and gender differences were assessed by one-way ANOVA, Chi-square, and Fisher exact tests. Data was analyzed using STATA version 13.0 (StataCorp, College Station, Texas, USA). Statistical significance was set at P < 0.05. RESULTS: Approximately 12% of the participants had normal occlusion, 57% had Class I malocclusion, 17% had Class II malocclusion, and 14% had Class III malocclusion. The highest prevalence of malocclusion traits was for displacement, followed by a crossbite. The IOTN results revealed slight need for orthodontic treatment in (n = 795-26%) moderate/borderline in (n = 1166-39%), and great need in (n = 1055-35%). Class II and III malocclusion, OJ, reverse overjet, scissor bite, open bite, midline discrepancies, and crowding were significantly higher in males than females (P < 0.05). CONCLUSION: Overall, there was a high prevalence of malocclusion and high orthodontic treatment need. The most common malocclusion was Class I. The most common orthodontic treatment need was moderate to borderline.